Research on Emergency Logistics Risk Analysis under Epidemic Based on HAZOP Technology - Zhao, Jinhu; Zhao, Zixiao (International Journal of Global Economics and Management, 2024)
This study explores using HAZOP analysis to assess risks in emergency logistics during epidemics. It highlights the importance of various aspects like personnel training and material management in different stages (preparation, rescue, and recovery) of emergency logistics. The study identifies critical risks through HAZOP analysis and proposes countermeasures like improved training and optimized resource allocation to mitigate these risks and improve overall efficiency. This research provides valuable guidance for building more robust emergency logistics systems to better respond to future outbreaks.